Ceramic tile with golden velvet texture and preparation method thereof

By designing a multi-layer structure glaze layer formula in ceramic tiles, the problem that existing ceramic tiles are difficult to form three-dimensional fine texture and texture is solved, and the high hardness, wear resistance and stain resistance of ceramic tiles are achieved.

CN119219428BActive Publication Date: 2025-02-28GUANGDONG NEWPEARL CERAMIC GRP CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411751802.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-02-28
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

Existing ceramic tiles with skin, velvet and velvet textures are difficult to form a three-dimensional fine concave and concave texture, which is similar to natural marble, and at the same time leads to the problems of low wear resistance and poor anti-fouling performance.

Method used

By designing a multi-layered ceramic tile, including a base glaze layer, a digital protective glaze layer and a surface glaze layer, a specific chemical composition and particle size formula is used to ensure that the glaze layer has a high temperature viscosity and delicate texture after firing, while maintaining the fineness and wear resistance of the texture.

Benefits of technology

It realizes that ceramic tiles have a fine concave and convex texture effect and a soft and delicate texture, while improving hardness, wear resistance and stain resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of ceramic technology, and specifically discloses a ceramic tile with a velvet texture and a preparation method thereof. The ceramic tile includes a base layer, a base glaze layer, a pattern layer, a functional ink layer, a digital protection glaze layer, and a surface glaze layer from bottom to top; the ceramic tile is obtained by firing the specially adjusted base glaze, digital protection glaze, and surface glaze applied in sequence. The present invention achieves the effect of a ceramic tile having both fine concave and convex texture effects and a soft and delicate texture by coordinating and improving the base glaze, digital protection glaze, and surface glaze formulas, and also has the characteristics of good hardness, wear resistance, and anti-fouling performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of ceramic technology, specifically relating to a ceramic tile with a velvet texture and its preparation method. Background Technology

[0002] With the development of matte ceramic tiles and consumers' growing fondness for them, matte ceramic tiles are not only pursuing beautiful textures and colors, but also innovating in the surface texture, constantly moving towards a delicate, warm, and soft touch. Currently, glazed ceramic tiles such as velvet, skin glaze, and smooth surface have appeared on the market, and their sales are getting better and better. The pursuit of a warm texture and delicate touch has also changed the cold and hard feeling that ceramic tiles used to give people, and has a good market prospect.

[0003] Currently, glazed tile production technology mainly involves adjusting the glaze formula to reduce the high-temperature viscosity of the glaze. After firing, the glaze surface is smoother and contains more glass phase, resulting in a delicate and warm effect, achieving a velvety, skin-like texture. However, consumers also greatly appreciate marble-like ceramic products. The fine, undulating texture of natural marble has a very natural effect, formed by the deposition of various elements and geological movements. Ceramic tiles can simulate this beautiful effect using inkjet digital inks to create finely textured seams. However, achieving the fine texture of natural marble requires a glaze with a slightly higher high-temperature viscosity and a slightly higher formulation temperature. As a result, when the glaze surface has a more three-dimensional texture, the glaze texture is relatively hard, making it difficult to achieve the warm, skin-like texture effect. Adjusting the glaze formula can give the glaze a warm, delicate, and smooth texture, but this often requires the addition of softer materials. After firing, these materials are prone to collapse, making it difficult to guarantee fine textures. Due to the use of soft materials in the glaze, the glaze's wear resistance and hardness are poor, resulting in poor stain resistance and making the tiles easily dirty, thus limiting the product's application range.

[0004] Therefore, addressing the challenge of creating ceramic tiles with skin-like, velvety, or glossy textures that lack the fine, three-dimensional textures reminiscent of natural marble, while simultaneously addressing the issue of low wear resistance and poor stain resistance caused by the delicate and warm glaze, is of great significance for improving product quality. Summary of the Invention

[0005] The purpose of this invention is to overcome the shortcomings of the prior art. Based on this, the first aspect of this invention provides a ceramic tile with a velvet texture, which, from bottom to top, includes a base layer, a base glaze layer, a pattern layer, a functional ink layer, a digital protective glaze layer, and a surface glaze layer.

[0006] The aforementioned base glaze layer is formed by a base glaze, which comprises, by weight, 4-8 parts of air-knife clay, 16-20 parts of calcined kaolin, 3-6 parts of calcined alumina, 10-15 parts of barium-containing frit, 15-23 parts of potassium feldspar, 12-20 parts of sodium feldspar, 12-18 parts of zirconium white frit, 3-6 parts of calcined talc, and 3-6 parts of wollastonite.

[0007] The aforementioned digital protective glaze layer is formed by a digital protective glaze, which comprises, by weight: 40-50 parts of organic solvent and 50-60 parts of inorganic glaze components; the aforementioned organic solvent comprises, by mass percentage: 45%-60% isooctyl laurate, 35%-50% ethyl acetate, 3%-6% dispersant, 0.1%-0.2% suspending agent, 0.2%-0.3% defoamer, 0.3%-0.6% leveling agent, and 0.15%-0.3% pH adjuster; the aforementioned inorganic glaze components comprise, by mass percentage: 17.35%-20.17% Al2O3, 55.68%-60.37% SiO2, 1.38%-2.65% K2O, 1.95%-3.01% Na2O, 2.13%-3.68% Bi2O3, 2.36%-4.65% BaO 4.37%-6.58%, SrO 3.65%-5.68%;

[0008] The above-mentioned surface glaze layer is formed by surface glaze, which includes, by weight, the following: 4-8 parts of spherical clay, 4-7 parts of corundum, 9-18 parts of high borosilicate frit, 18-25 parts of boron bismuth frit, 30-45 parts of monovalent oxide frit, 6-10 parts of barium carbonate, and 6-10 parts of strontium carbonate.

[0009] The average particle size of the particles in the base glaze is 2 μm-8 μm; the average particle size of the particles in the digital protective glaze is 50 nm-100 nm; and the average particle size of the particles in the surface glaze is 1 μm-8 μm.

[0010] This invention achieves the effect of ceramic tiles having both fine textured surface and smooth, delicate feel through the overall research and design of the base glaze, digital protective glaze and surface glaze. It also has good hardness, wear resistance and stain resistance.

[0011] The surface glaze, being the layer directly in contact with the external environment, requires good physical properties, a smooth, warm, and delicate texture, and fine surface patterns. Currently, there is no glaze formula that can simultaneously achieve all these effects. In this invention, the surface glaze uses spherical clay primarily to ensure the suspension of the glaze slurry, prevent sedimentation, and provide the main framework components Al2O3 and SiO2. The corundum used is calcined Al2O3, characterized by high hardness and chemical stability. Compared to Al2O3, it is more conducive to improving the glaze's transparency (transparency is extremely important for surface glazes, ensuring clear display of patterns). The high-purity silicon frit used (a frit made primarily of SiO2 and boron trioxide, with main components by mass percentage including: Al2O3 13.25%-15.35%, SiO2 68.39%-71.25%, B2O3 8.67%-11.25%, K2O) is also used. 2.35%-4.67%, Na2O 1.54%-2.68%, the remainder being trace impurities and reduced as appropriate) and the boron-bismuth frit used (the main components, by mass percentage, include: SiO2 56.31%-60.37%, Al2O3 13.64%-15.77%, B2O3 11.32%-14.65%, Bi2O3 8.62%-9.67%, K2O 1.35%-2.91%, Na2O The glaze contains 1.11%-2.08% boron-oxygen tetrahedra, with the remainder being trace impurities and subject to reduction. This primarily utilizes boron-oxygen tetrahedra to replace some silicon-oxygen tetrahedra, thereby increasing the hardness of the glaze layer. Simultaneously, the presence of bismuth oxide fills the glass phase, replacing some Al2O3, resulting in a more smooth and delicate glaze layer. Furthermore, it maintains the high-temperature viscosity of the glaze after firing, ensuring the glaze layer retains its fine texture. The monovalent oxide frit used (its main components, by mass percentage, include: K2O 4.56%-6.67%, Na2O 6.21%-9.34%, Li2O 4.63%-6.46%, SiO2 59.31%-63.34%, Al2O3) (16.69%-18.35%, the remainder being trace impurities and reduced as appropriate) mainly utilizes the low-temperature fluxing effect of its monovalent oxides to promote the full reaction of the glaze layer, forming a glassy phase and increasing the smoothness of the glaze layer; while the barium carbonate and strontium carbonate used can form barium strontium ice crystals after firing, which have the characteristics of a layered structure, enabling the glaze surface to have a smooth texture.The overall chemical composition of the surface glaze, by mass percentage, includes: Al2O3 15.38%-17.65%, SiO2 52.21%-54.61%, K2O 2.31%-3.45%, Na2O 1.35%-2.45%, Li2O 1.02%-1.89%, B2O3 6.65%-8.58%, Bi2O3 3.65%-5.94%, BaO 4.31%-5.98%, SrO 4.64%-5.75%, with the remainder being trace impurities and reduced as appropriate.

[0012] Secondly, based on the specially designed surface glaze, this invention also conducts special research and design on the composition of the base glaze. In the base glaze formula of this invention, the air-knife clay mainly provides aluminum oxide and SiO2 as the main framework, while having good suspension properties to ensure that the glaze does not settle. The calcined kaolin used is to provide aluminum oxide and SiO2 as the main framework. At the same time, when the calcined kaolin is applied to the glaze, it has less shrinkage after firing, resulting in a denser and finer glaze layer. The barium-containing frit used is a frit made from BaO oxides, mainly providing BaO. During firing, it can interact with the digital protective glaze and the surface glaze to form barium strontium ice crystals, which have a layered structure. Furthermore, it exists not only in the surface glaze layer but also in the base glaze layer, solving the problem of the relatively hard base of conventional glazes. The main function of the potassium feldspar and sodium feldspar used is to provide monovalent oxides, which accelerates the firing speed and is conducive to crystal formation. The main function of the zirconium white frit used is to increase the whiteness of the glaze layer and cover the color of the base layer. Moreover, the introduction of ZrO2 in the form of zirconium white frit, compared with the more common method of introducing zirconium silicate, not only has better covering ability but also better melting properties, which can avoid the problem of rough glaze surface caused by zirconium silicate. The calcined talc used mainly provides alkaline earth metal oxide MgO, which has a good high-temperature fluxing effect and makes the glaze surface smoother after firing.

[0013] Furthermore, this invention also includes a digital protective glaze layer containing a specifically formulated digital protective glaze between the aforementioned base glaze layer and the aforementioned surface glaze layer. The average particle size (50 nm-100 nm) of the particles in the digital protective glaze is smaller than that of the base glaze (average particle size 2 μm-8 μm) and the surface glaze (average particle size 1 μm-8 μm), allowing the particles in the digital protective glaze to effectively fill the gaps between the other two layers, resulting in a denser glaze layer. After firing, the various crystalline phases are evenly distributed, making the overall glaze layer more delicate and smooth. In the aforementioned digital protective glaze, monovalent oxides mainly act as fluxes, while alkaline earth metal oxides and neutral oxides Bi₂O₃ and B₂O₃ enable the digital protective glaze to bond more completely with the base glaze and surface glaze, resulting in a more suitable acidity coefficient.

[0014] The organic solvents mentioned above, by mass percentage, include: 45%-60% isooctyl laurate, 35%-50% ethyl acetate, 3%-6% dispersant, 0.1%-0.2% suspending agent, 0.2%-0.3% defoamer, 0.3%-0.6% leveling agent, and 0.15%-0.3% pH adjuster.

[0015] The chemical composition of the aforementioned base glaze, by mass percentage, includes: Al₂O₃ 21.04%-24.56%, SiO₂ 50.24%-53.29%, K₂O 1.34%-2.57%, Na₂O 1.87%-2.65%, CaO 0.80%-1.61%, MgO 1.21%-2.04%, BaO 6.31%-8.24%, and ZrO₂ 6.30%-8.64%. The aforementioned base glaze layer is formed by preparing a first slurry from the aforementioned base glaze. The preparation method of the first slurry includes the following steps: mixing the aforementioned base glaze with 38-40 parts of water, 0.13-0.18 parts of sodium carboxymethyl cellulose, and 0.25-0.35 parts of sodium tripolyphosphate, and ball milling to obtain the aforementioned first slurry.

[0016] The aforementioned surface glaze layer is formed by preparing a second slurry from the aforementioned surface glaze. The preparation method of the aforementioned second slurry includes the following process: mixing the aforementioned surface glaze with 38-40 parts of water, 0.15-0.2 parts of sodium carboxymethyl cellulose, and 0.3-0.4 parts of sodium tripolyphosphate, and ball milling to obtain the aforementioned second slurry.

[0017] A second aspect of the present invention provides a method for preparing the above-mentioned ceramic tile with a velvet texture, comprising the following steps: applying the above-mentioned base glaze to the above-mentioned base layer, then sequentially printing a pattern and functional ink, followed by applying the above-mentioned digital protective glaze and applying the above-mentioned surface glaze; and firing to obtain the above-mentioned ceramic tile.

[0018] The moisture content of the aforementioned base layer is less than 0.3%, and its strength is 1.8 MPa-2.4 MPa; the application amount of the aforementioned base glaze is 380 g / m². 2 -450 g / m 2 The application amount of the aforementioned digital protective glaze is 70 g / m². 2 -100 g / m 2 The application amount of the above-mentioned surface glaze is 180 g / m². 2 -240 g / m 2 The firing conditions mentioned above include: firing time of 50 min-60 min and firing temperature of 1180 ℃-1190 ℃.

[0019] It should be noted that all "%" in this invention refers to "mass percentage", which is equivalent to "mass percentage content" and "mass fraction"; it should also be noted that "applying glaze" in this field is equivalent to "slurry made by applying glaze", which is common knowledge to those skilled in the art and will not cause any ambiguity or misunderstanding, nor will it affect the understanding and implementation of the technical solution.

[0020] The beneficial effects of this invention are as follows: By coordinating and improving the formulations of the base glaze, digital protective glaze, and surface glaze, this invention achieves the effect of ceramic tiles having both a fine textured surface and a smooth and delicate feel, while also having good hardness, wear resistance, and stain resistance. Attached Figure Description

[0021] Figure 1 The image shown is of a ceramic tile with a velvet texture prepared in Example 1.

[0022] Figure 2 The image shown is of the ceramic tile prepared in Comparative Example 1.

[0023] Figure 3 The diagram shows the structure of the ceramic tile with a velvet texture prepared in Example 1. Detailed Implementation

[0024] The following will provide a clear and complete description of the concept, specific structure, and technical effects of the present invention in conjunction with embodiments and accompanying drawings, so as to fully understand the purpose, solution, and effects of the present invention. It should be noted that, unless otherwise specified, the embodiments and features described in the embodiments of the present invention can be combined with each other.

[0025] Example 1

[0026] A ceramic tile with a velvet texture, its structural diagram is shown below. Figure 3 As shown, from bottom to top, it includes a base layer, a base glaze layer, a pattern layer, a functional ink layer, a digital protective glaze layer, and a surface glaze layer.

[0027] The base glaze layer is formed from a first slurry made from the base glaze. The base glaze, by weight, comprises: 6 parts air-knife clay, 18 parts calcined kaolin, 4.5 parts calcined alumina, 12.5 parts barium-containing frit, 19 parts potassium feldspar, 16 parts sodium feldspar, 15 parts zirconium frit, 4.5 parts calcined talc, and 4.5 parts wollastonite. Its chemical composition, by mass percentage, includes: Al₂O₃ 22.80%, SiO₂ 51.76%, K₂O 1.95%, Na₂O 2.26%, CaO 1.20%, MgO 1.62%, BaO 7.27%, and ZrO₂ 7.47%. The preparation process of the first slurry includes: mixing the above-mentioned base glaze with 38 parts of water, 0.15 parts of sodium carboxymethyl cellulose and 0.3 parts of sodium tripolyphosphate, and ball milling to obtain the first slurry; the average particle size of the particles in the first slurry (that is, the average particle size of the base glaze) is 4 μm-6 μm.

[0028] The digital protective glaze layer is formed by the digital protective glaze, which, by weight, comprises: 45 parts organic solvent and 55 parts inorganic glaze components. The organic solvent, by mass percentage, comprises: 52% isooctyl laurate, 43% ethyl acetate, 4% dispersant (sodium polyacrylate), 0.15% suspending agent (hexamethyldisilazane), 0.25% defoamer (ethylene glycol), 0.4% leveling agent (Taiyang TY01), and 0.2% pH adjuster (triethanolamine). The inorganic glaze components, by mass percentage, comprise: 18.76% Al₂O₃, 58.02% SiO₂, 2.01% K₂O, 2.48% Na₂O, 2.9% Bi₂O₃, 3.50% B₂O₃, 5.47% BaO, and 4.66% SrO. The average particle size of the digital protective glaze (i.e., the average particle size of the inorganic glaze components) is 70 nm.

[0029] The surface glaze layer is formed by a second slurry made from the surface glaze. The surface glaze, by weight, comprises: 6 parts spherical clay, 5.5 parts corundum, 13.5 parts high borosilicate frit, 21.5 parts boron bismuth frit, 37.5 parts monovalent oxide frit, 8 parts barium carbonate, and 8 parts strontium carbonate. Its chemical composition, by mass percentage, includes: Al₂O₃ 16.51%, SiO₂ 53.41%, K₂O 2.88%, Na₂O 1.90%, Li₂O 1.45%, B₂O₃ 7.61%, Bi₂O₃ 4.79%, BaO 5.14%, and SrO 5.19%. The preparation process of the second slurry includes: mixing the above-mentioned surface glaze with 39 parts of water, 0.15 parts of sodium carboxymethyl cellulose and 0.4 parts of sodium tripolyphosphate, and ball milling to obtain the second slurry; the average particle size of the particles in the second slurry (that is, the average particle size of the surface glaze) is 3 μm-5 μm.

[0030] The preparation method of this ceramic tile with a velvety texture includes the following steps:

[0031] The brick blanks are pressed to form the base layer, which is then dried to a moisture content of 0.3% and a strength of 2.1 MPa. A base glaze is then applied to the base layer at a rate of 420 g / m². 2 The inkjet printer then prints fine-textured marble-like patterns and functional inks. Following this, a second inkjet printer prints a digital protective glaze, with a print volume of 80 g / m³. 2 Then, the surface glaze is applied using a spraying equipment at a rate of 200 g / m². 2 Finally, it is fired in a kiln for 58 minutes at a temperature of 1180 ℃. After firing, the edges are ground to obtain the ceramic tile with a velvety texture. Product photos are shown below. Figure 1 As shown, it has the effect of velvet texture and undulating patterns, which can reproduce the effect of marble.

[0032] Example 2

[0033] A ceramic tile with a velvety texture differs from Example 1 in that: the base glaze contains 10 parts of barium frit; the chemical composition of the base glaze, by mass percentage, includes: Al2O3 23.50%, SiO2 51.96%, K2O 1.94%, Na2O 2.28%, CaO 1.22%, MgO 1.63%, BaO 6.31%, ZrO2 7.51%. All other aspects are the same as in Example 1.

[0034] Example 3

[0035] A ceramic tile with a velvety texture differs from Example 1 in that: the base glaze contains 15 parts of barium frit; the chemical composition of the base glaze, by mass percentage, includes: Al2O3 22.60%, SiO2 50.81%, K2O 1.93%, Na2O 2.17%, CaO 1.18%, MgO 1.58%, BaO 8.21%, ZrO2 7.39%. All other aspects are the same as in Example 1.

[0036] Example 4

[0037] A ceramic tile with a velvety texture, which differs from Example 1 in that the average particle size of the base glaze is 2 μm. Otherwise, it is the same as Example 1.

[0038] Example 5

[0039] A ceramic tile with a velvety texture, which differs from Example 1 in that the average particle size of the base glaze is 8 μm. Otherwise, it is the same as Example 1.

[0040] Example 6

[0041] A ceramic tile with a velvet texture, which differs from Example 1 in that the Bi2O3 content in the digital protective glaze is 2.13%. Everything else is the same as in Example 1.

[0042] Example 7

[0043] A ceramic tile with a velvet texture, which differs from Example 1 in that the Bi2O3 content in the digital protective glaze is 3.68%. Everything else is the same as in Example 1.

[0044] Example 8

[0045] A ceramic tile with a velvety texture differs from Example 1 in that the B2O3 content in the digital protective glaze is 2.36%. Otherwise, it is the same as Example 1.

[0046] Example 9

[0047] A ceramic tile with a velvet texture, which differs from Example 1 in that the B2O3 content in the digital protective glaze is 4.65%. Otherwise, it is the same as Example 1.

[0048] Example 10

[0049] A ceramic tile with a velvety texture, differing from Example 1 in that the average particle size of the digital protective glaze is 50 nm. Otherwise, it is the same as Example 1.

[0050] Example 11

[0051] A ceramic tile with a velvety texture, differing from Example 1 in that the average particle size of the digital protective glaze is 100 nm. Otherwise, it is the same as Example 1.

[0052] Example 12

[0053] A ceramic tile with a velvety texture differs from Example 1 in that: the surface glaze contains 9 parts of high borosilicate frit; the chemical composition of the surface glaze, by mass percentage, includes: Al2O3 17.51%, SiO2 52.21%, K2O 2.81%, Na2O 1.88%, Li2O 1.39%, B2O3 6.68%, Bi2O3 5.69%, BaO 5.12%, and SrO 5.29%. All other aspects are the same as in Example 1.

[0054] Example 13

[0055] A ceramic tile with a velvety texture differs from Example 1 in that: the surface glaze contains 18 parts of high borosilicate frit; the chemical composition of the surface glaze, by mass percentage, includes: Al2O3 15.98%, SiO2 54.61%, K2O 2.98%, Na2O 1.80%, Li2O 1.40%, B2O3 8.58%, Bi2O3 3.68%, BaO 5.02%, and SrO 4.94%. All other aspects are the same as in Example 1.

[0056] Example 14

[0057] A ceramic tile with a velvety texture differs from Example 1 in that: the surface glaze contains 18 parts of boron-bismuth frit; the chemical composition of the surface glaze, by mass percentage, includes: Al₂O₃ 17.05%, SiO₂ 53.61%, K₂O 2.94%, Na₂O 2.01%, Li₂O 1.35%, B₂O₃ 6.68%, Bi₂O₃ 3.67%, BaO 4.88%, and SrO 5.05%. All other aspects are the same as in Example 1.

[0058] Example 15

[0059] A ceramic tile with a velvety texture differs from Example 1 in that: the surface glaze contains 25 parts of boron-bismuth frit; the chemical composition of the surface glaze, by mass percentage, includes: Al₂O₃ 16.28%, SiO₂ 53.25%, K₂O 2.71%, Na₂O 1.85%, Li₂O 1.42%, B₂O₃ 8.48%, Bi₂O₃ 5.88%, BaO 4.67%, and SrO 4.90%. All other aspects are the same as in Example 1.

[0060] Example 16

[0061] A ceramic tile with a velvety texture, differing from Example 1 in that the average particle size of the surface glaze particles is 1 μm. Otherwise, it is the same as Example 1.

[0062] Example 17

[0063] A ceramic tile with a velvety texture, differing from Example 1 in that the average particle size of the surface glaze is 8 μm. Otherwise, it is the same as Example 1.

[0064] Comparative Example 1

[0065] A ceramic tile differs from Example 1 in that: the base glaze contains 8 parts of barium frit; the chemical composition of the base glaze, by mass percentage, includes: Al2O3 23.70%, SiO2 52.36%, K2O 2.15%, Na2O 3.06%, CaO 1.21%, MgO 1.42%, BaO 6.21%, ZrO2 6.77%. All other aspects are the same as in Example 1.

[0066] Comparative Example 2

[0067] A ceramic tile differs from Example 1 in that: the base glaze contains 17 parts of barium frit; the chemical composition of the base glaze, by mass percentage, includes: Al2O3 21.70%, SiO2 51.86%, K2O 1.90%, Na2O 2.28%, CaO 1.29%, MgO 1.64%, BaO 10.20%, and ZrO2 7.38%. All other aspects are the same as in Example 1.

[0068] Comparative Example 3

[0069] A ceramic tile differs from Example 1 in that the average particle size of the base glaze is 0.8 μm. Otherwise, it is the same as Example 1.

[0070] Comparative Example 4

[0071] A ceramic tile differs from Example 1 in that the average particle size of the base glaze is 20 μm. Otherwise, it is the same as Example 1.

[0072] Comparative Example 5

[0073] A ceramic tile differs from Example 1 in that the Bi2O3 content in the digital protective glaze is 1.89%. Otherwise, it is the same as Example 1.

[0074] Comparative Example 6

[0075] A ceramic tile differs from Example 1 in that the Bi2O3 content in the digital protective glaze is 4.01%. Otherwise, it is the same as Example 1.

[0076] Comparative Example 7

[0077] A ceramic tile differs from Example 1 in that the B2O3 content in the digital protective glaze is 2.05%. Otherwise, it is the same as Example 1.

[0078] Comparative Example 8

[0079] A ceramic tile differs from Example 1 in that the B2O3 content in the digital protective glaze is 4.87%. Otherwise, it is the same as Example 1.

[0080] Comparative Example 9

[0081] A ceramic tile differs from Example 1 in that the average particle size of the digital protective glaze is 150 nm. Otherwise, it is the same as Example 1.

[0082] Comparative Example 10

[0083] A ceramic tile differs from Example 1 in that: the surface glaze contains 7 parts of high borosilicate frit; the chemical composition of the surface glaze, by mass percentage, includes: Al₂O₃ 18.55%, SiO₂ 50.11%, K₂O 3.55%, Na₂O 2.56%, Li₂O 1.95%, B₂O₃ 4.15%, Bi₂O₃ 4.65%, BaO 5.11%, and SrO 4.95%. All other aspects are the same as in Example 1.

[0084] Comparative Example 11

[0085] A ceramic tile differs from Example 1 in that: the surface glaze contains 20 parts of high borosilicate frit; the chemical composition of the surface glaze, by mass percentage, includes: Al₂O₃ 15.38%, SiO₂ 55.66%, K₂O 2.35%, Na₂O 1.36%, Li₂O 1.36%, B₂O₃ 9.28%, Bi₂O₃ 3.99%, BaO 4.69%, and SrO 4.89%. All other aspects are the same as in Example 1.

[0086] Comparative Example 12

[0087] A ceramic tile differs from Example 1 in that: the surface glaze contains 16 parts of boron-bismuth frit; the chemical composition of the surface glaze, by mass percentage, includes: Al₂O₃ 18.75%, SiO₂ 55.61%, K₂O 2.47%, Na₂O 1.74%, Li₂O 1.47%, B₂O₃ 4.55%, Bi₂O₃ 2.55%, BaO 4.96%, and SrO 5.05%. All other components are the same as in Example 1.

[0088] Comparative Example 13

[0089] A ceramic tile differs from Example 1 in that: the surface glaze contains 27 parts of boron-bismuth frit; the chemical composition of the surface glaze, by mass percentage, includes: Al₂O₃ 15.31%, SiO₂ 51.35%, K₂O 2.70%, Na₂O 1.64%, Li₂O 1.34%, B₂O₃ 9.50%, Bi₂O₃ 6.44%, BaO 4.75%, and SrO 4.63%. All other aspects are the same as in Example 1.

[0090] Comparative Example 14

[0091] A ceramic tile differs from Example 1 in that the average particle size of the surface glaze particles is 0.8 μm. Otherwise, it is the same as Example 1.

[0092] Comparative Example 15

[0093] A ceramic tile differs from Example 1 in that the average particle size of the surface glaze particles is 10 μm. Otherwise, it is the same as Example 1.

[0094] The ceramic tiles of Examples 1-17 and Comparative Examples 1-15 were tested, mainly examining the fineness of the glaze texture and the fineness of the glaze seams, wear resistance, hardness, and stain resistance. The fineness of the glaze and the fineness of the seams were determined primarily through subjective observation and comparison. The wear resistance was tested according to the specifications in the ceramic tile testing standard GB / T4100—2015.

[0095] Hardness testing methods: For glaze hardness, the Mohs hardness test is used. A Mohs hardness test mineral is embedded in a pen-shaped testing tool on a metal rod. The mineral's edge is used to scratch the object being tested. The hardness is determined by whether a scratch is left: if a scratch is left, the object's hardness is lower than the hardness pen; if no scratch is left, the object's hardness is higher than the hardness pen. The corresponding levels for the testing materials used in the Mohs hardness test are: Talc: Level 1, Gypsum: Level 2, Calcite: Level 3, Fluorite: Level 4, Apatite: Level 5, Feldspar: Level 6, Quartz: Level 7, Topaz: Level 8, Corundum: Level 9, Diamond: Level 10.

[0096] The testing method for stain resistance is based on the provisions of the ceramic tile testing standard GB / T4100—2015.

[0097] The test results of ceramic tiles in each embodiment and comparative example are shown in Tables 1, 2 and 3.

[0098] Table 1

[0099]

[0100] Table 2

[0101]

[0102] Table 3

[0103]

[0104] As can be seen from Tables 1-3, in Comparative Example 1, the base glaze formula used less barium frit, resulting in fewer crystals forming a smooth texture after firing, thus causing the glaze surface to be less delicate and smooth. Figure 2As shown in the figures: Comparative Example 2 contained a high amount of barium frit, which resulted in excessive melting and shrinkage after firing, causing an uneven glaze surface. In Comparative Example 3, the base glaze was too fine, leading to excessive shrinkage during firing and an uneven glaze surface. In Comparative Example 4, the base glaze was too fine, resulting in insufficient liquid phase formation during firing and a rough, uneven, and non-smooth glaze surface. In Comparative Example 5, the digital protective glaze contained too little bismuth trioxide, failing to fill the gaps in the glass phase and resulting in a less smooth glaze surface. In Comparative Example 6, the digital protective glaze contained too much bismuth trioxide, resulting in a less smooth and warm glaze surface, and the texture was not three-dimensional enough. In Comparative Example 7, the digital protective glaze contained too little boron, affecting the product's wear resistance and hardness. In Comparative Example 8, the digital protective glaze contained too much boron, which had the opposite effect, resulting in a dry glaze surface, low wear resistance, and a less three-dimensional texture. In Comparative Example 9, the digital protective glaze particles were too coarse, resulting in larger gaps on the glaze surface after firing, leading to a coarse glaze surface. This also affected the maturity of the glaze after firing, resulting in lower wear resistance and hardness. In Comparative Example 10, the amount of high borosilicate frit in the surface glaze was too small, resulting in a low boron content that directly affected the hardness and wear resistance of the glaze surface, and also resulted in a poor texture. In Comparative Example 11, the content of high borosilicate frit in the surface glaze was too large, resulting in excessive oxides and a higher temperature formulation. After firing, the glaze surface was not fine enough, and its performance in all aspects was poor. In Comparative Example 12, the content of boron-bismuth frit in the surface glaze was too small, resulting in less boron and bismuth oxides. The formed glass phase was mainly composed of potassium-sodium glass phase, resulting in lower wear resistance and hardness of the glaze surface. At the same time, the glaze surface was dry and rough due to the lack of oxides. In Comparative Example 13, the content of boron-bismuth frit in the surface glaze was too large, and the formulation temperature was too low, resulting in a mismatch. After firing, the glaze surface was uneven, and its wear resistance and hardness were also low. In Comparative Example 14, the surface glaze particles are relatively fine, resulting in large shrinkage after firing, affecting the smoothness of the glaze surface and the lack of a three-dimensional texture, while also affecting various physical properties of the glaze surface. In Comparative Example 15, the surface particles are relatively coarse, directly causing a rough glaze surface after firing. At the same time, due to insufficient sintering, the wear resistance and hardness are insufficient, and the texture is not three-dimensional or refined enough.

[0105] The above description is merely a preferred embodiment of the present invention. The present invention is not limited to the above-described embodiments. Any embodiment that achieves the technical effects of the present invention using the same means should fall within the protection scope of the present invention. Within the protection scope of the present invention, various modifications and variations can be made to the technical solutions and / or implementation methods.

Claims

1. A ceramic tile with a gold velvet texture, characterized in that: From bottom to top, it includes base layer, base glaze layer, pattern layer, functional ink layer, digital protection glaze layer, and surface glaze layer; The base glaze layer is formed by a base glaze, and the base glaze comprises, by weight: 4-8 parts of air knife clay, 16-20 parts of calcined kaolin, 3-6 parts of calcined alumina, 10-15 parts of barium-containing frit, 15-23 parts of potassium feldspar, 12-20 parts of sodium feldspar, 12-18 parts of zircon white frit, 3-6 parts of burned talc, and 3-6 parts of wollastonite; The digital protection glaze layer is formed by a digital protection glaze, and the digital protection glaze comprises, by weight: 40-50 parts of an organic solvent and 50-60 parts of an inorganic glaze component; the inorganic glaze component comprises, by weight percentage: Al2O3 17.35%-20.17%, SiO2 55.68%-60.37%, K2O 1.38%-2.65%, Na2O 1.95%-3.01%, Bi2O3 2.13%-3.68%, B2O3 2.36%-4.65%, BaO 4.37%-6.58%, SrO 3.65%-5.68%; The surface glaze layer is formed by a surface glaze, and the surface glaze comprises, by weight: 4-8 parts of ball clay, 4-7 parts of corundum, 9-18 parts of high borosilicate frit, 18-25 parts of boron bismuth frit, 30-45 parts of monovalent oxide frit, 6-10 parts of barium carbonate, and 6-10 parts of strontium carbonate; The average particle size of the particles in the base glaze is 2 μm-8 μm; the average particle size of the particles in the digital protection glaze is 50nm-100 nm; the average particle size of the particles in the surface glaze is 1 μm-8 μm; The chemical components of the base glaze include, by mass percentage: Al2O3 21.04%-24.56%, SiO2 50.24%-53.29%, K2O 1.34%-2.57%, Na2O 1.87%-2.65%, CaO 0.80%-1.61%, MgO 1.21%-2.04%, BaO6.31%-8.24%, ZrO2 6.30%-8.64%; The chemical components of the high borosilicate frit include, by mass percentage: Al2O3 13.25%-15.35%, SiO2 68.39%-71.25%, B2O3 8.67%-11.25%, K2O 2.35%-4.67%, Na2O 1.54%-2.68%; The chemical components of the boron-bismuth frit include, by mass percentage, SiO2 56.31%-60.37%, Al2O3 13.64%-15.77%, B2O3 11.32%-14.65%, Bi2O3 8.62%-9.67%, K2O 1.35%-2.91%, and Na2O 1.11%-2.08%.

2. The ceramic tile according to claim 1, characterized in that: The base glaze layer is formed by making the base glaze into a first slurry, and the preparation method of the first slurry is The method comprises the following steps: mixing the base glaze with 38-40 parts of water, 0.13-0.18 parts of sodium carboxymethyl cellulose and 0.25-0.35 parts of sodium tripolyphosphate, and performing ball milling to obtain the first slurry.

3. The ceramic tile according to claim 1, characterized in that: The chemical components of the monovalent oxide frit include, by mass percentage, K2O 4.56%-6.67%, Na2O 6.21%-9.34%, Li2O 4.63%-6.46%, SiO2 59.31%-63.34%, and Al2O3 16.69%-18.35%.

4. The ceramic tile according to claim 1, characterized in that: The chemical components of the surface glaze include, by mass percentage, Al2O3 15.38%-17.65%, SiO2 52.21%-54.61%, K2O 2.31%-3.45%, Na2O 1.35%-2.45%, Li2O 1.02%-1.89%, B2O3 6.65%-8.58%, Bi2O3 3.65%-5.94%, BaO 4.31%-5.98%, and SrO 4.64%-5.75%.

5. The ceramic tile according to claim 1, characterized in that: The surface glaze layer is formed by making the surface glaze into a second slurry, and the preparation method of the second slurry is The method comprises the following steps: mixing the surface glaze with 38-40 parts of water, 0.15-0.2 parts of sodium carboxymethyl cellulose and 0.3-0.4 parts of sodium tripolyphosphate, and performing ball milling to obtain the second slurry.

6. A method for preparing a ceramic tile according to any one of claims 1 to 5, characterized in that: The following steps are involved: Applying the base glaze on the base layer, then printing patterns and functional inks in sequence, and then applying the digital protective glaze and the surface glaze; The ceramic brick is obtained by firing.

7. The preparation method according to claim 6, characterized in that: The moisture content of the base layer is less than 0.3%, and the strength is 1.8 MPa-2.4 MPa; and / or the application amount of the base glaze is 380 g / m 2 -450 g / m 2 ; and / or, the application amount of the digital protective glaze is 70 g / m 2 -100 g / m 2 ; and / or, the application amount of the surface glaze is 180 g / m 2 -240 g / m 2 ; And / or, the firing conditions include: a firing time of 50 min-60 min and a firing temperature of 1180°C-1190°C.

Citation Information

Patent Citations

  • Self-releasing glaze ceramic and preparation method thereof

    CN111825428A

  • Wear-resistant antifouling protective glaze, matte ceramic tile and preparation method of matte ceramic tile

    CN114853346A